Using Environmental Isotopes for Water Resources Evaluation in Altun Kopri Basin, NE Kirkuk - A. A. Alabadi, Mazin; M. Alshamma’a, Ayser (Iraqi Journal of Science, 2023)
Recently, the environmental isotopes are adopted to figure out the hydrological processes, recharge areas, flow paths, groundwater origin and the interaction between different watery bodies. Currently, five samples of the rainwater have been collected since January to April 2012, as well as December 2011. Those sampling periods have highest amounts of precipitation events. Meantime, 25 samples of groundwater, 5 of the Lesser Zab River and 3 of overland flow have been picked up during the wet period. The dry sampling of groundwater and the Lesser Zab River has been achieved in summer 2011. The Local Meteoric Water Line lies between Global Meteoric Water Line (GMWL) and East Mediterranean Water Line (EMWL). The lowest, highest and average of δ18O in precipitation are -4.00‰, -3.60‰ and -3.84‰, while δ2H equal to -17.20‰, -14.00‰ and -15.60‰ respectively. The ranges of δ18O and δ2H of the Lesser Zab River in dry period are -3.12‰ to -2.82‰ and -12.80‰ to -12.00‰ sequentially. In the wet period, runoff samples are added to the Lesser Zab River. The lowest and highest of δ18O are -5.30‰ and -4.87‰ respectively, while δ2H extends from -30.00‰ to -28.65‰. Groundwater samples have δ18O and δ2H increased with well depths somewhat. Signatures of the wells have been fallen into two groups within two sampling campaigns; dry and wet periods. The first well samples are dropped above the GMWL and the second samples are classified below the GMWL.